Autism spectrum disorder screening with the CBCL/1½–5: Findings for young children at high risk for autism spectrum disorder. (January 2019) - Rescorla, Leslie A; Winder-Patel, Breanna M; Paterson, Sarah J; Pandey, Juhi; Wolff, Jason J; Schultz, Robert T; Piven, Joseph
The screening power of the CBCL/1½–5's Withdrawn and Diagnostic and Statistical Manual of Mental Disorders -Pervasive Developmental Problems (DSM-PDP) scales to identify children diagnosed with autism spectrum disorder at 24 months was tested in a longitudinal, familial high-risk study. Participants were 56 children at high risk for autism spectrum disorder due to an affected older sibling (high-risk group) and 26 low-risk children with a typically developing older sibling (low-risk group). At 24 months, 13 of the 56 high-risk children were diagnosed with autism spectrum disorder, whereas the other 43 were not. The high-risk children diagnosed with autism spectrum disorder group had significantly higher scores on the CBCL/1½–5's Diagnostic and Statistical Manual of Mental Disorders -Pervasive Developmental Problems and Withdrawn scales than children in the low-risk and high-risk children not diagnosed with autism spectrum disorder groups( η p 2 > 0 . 50 ) . Receiver operating characteristic analyses yielded very high area under the curve values (0.91 and 0.89), and a cut point of T  ⩾ 60 yielded sensitivity of 77% and specificity of 97% to 99% between the high-risk children diagnosed with autism spectrum disorder and the combination of low-risk and high-risk children not diagnosed with autism spectrum disorder. Consistent with several previous studies, the CBCL/1½–5's Diagnostic and Statistical Manual of Mental Disorders -Pervasive Developmental Problems scale and the Withdrawn syndrome differentiated well between children diagnosed with autism spectrum disorder and those not diagnosed.